(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
Linguistic arguments allow us to think that Ossonoba, Murtili and Baesuri belong to the same pre-Roman toponymy as that of neighboring Andalusia. The fact that they are Latinized forms is not an obstacle to this.